The Reproductive Health of the Philippines: Perceptions in the South - A, SITTIE AKIMA (Universitas Muhammadiyah Yogyakarta, 2018)
This is a descriptive and correlational study that focuses on determining the level of awareness and attitudes of the respondents toward the reproductive health program of the Philippines. It tried to test the hypotheses whether there is significant relationship between the respondents’ socio-economic profile such as age, gender, education, annual income, work type, and number of children and their level of awareness and attitude towards the reproductive health program.The study found that majority of the respondents are aware and have positive attitude toward the RH Law which can be partly attributed to their place of employment which is an academic institution and where the reproductive health issue is expected to be subjected to thorough discussions.It is concluded that the respondents have favourable and positive reactions on the RH Law, hence it is necessary for the government to pursue it with due respect to religion and cultural beliefs of the Filipinos especially among the Catholics. It is recommended that awareness drives and information dissemination on the positive effects of the RH Bill should be continued, not only in schools but also in communities where most poor families live.